The Escalation of Gambling in Papua New Guinea, 1936–1971: Notable absence to national obsession. Issue 1 (1st January 2021) - Pickles, Anthony J.
ABSTRACT: Future Papua New Guineans (PNG) start gambling from the 1880s. Gambling was then made illegal (for them but not for their colonizers). It takes off during World War II, becoming ubiquitous knowledge by the late 1970s, just after Papua New Guineans achieve independence from Australia. As incidence accelerates gambling relationships proliferate until they plateau at saturation point. This exciting, liberating, unpredictable cloud of activity became a threat to the prospect of an ordered, advancing independent modern nation-state. PNG legislators responded by banning playing cards completely. This is suggested as evidence of an 'escalation' because gambling became something new, a vehicle for imagining the nation as a truly connected whole through this relational technology, even if the image was an uneasy one. As the escalation occurred the acceleration plateaued once new recruits dried up and as economic development failed to materialize, revealing some useful socio-material guardrails for an anthropology of escalation.